Novas contribuicões ao conhecimento do gênero Procamallanus (Nematoda, Camallanoidea) On Brazilian "Procamallanus" - R. Magalhães Pinto; Sueli P. de Fabio; Dely Noronha; F. J. Tayt-Son Rolas (Memorias do Instituto Oswaldo Cruz, 1975)
Os autores, continuando com o estudo dos Procamallanus brasileiros, propõem Procamallanus (S.) solaini como espécie nova para o gênero. Redescrevem Procamallanus (S.) iheringi Travassos, Artigas & Pereira, 1928, depois de terem tido acesso ao material tipo e elucidado dúvidas a respeito de sua morfologia. Para Procamallanus (S.) inopinatus Travassos, Artigas & Pereira, 1928, tiveram a descrição de Pinto & Noronha, 1972 adaptada. De Procamallanus (S.) amarali Vas & Pereira, 1934, tornam conhecida a fêmea da espécie e fazem uma breve redescrição do macho. Listam amostras de Procamallanus sp. que não conduziram a um diagnóstico preciso, devido ao seu precário estado de conservação. Foram examinadas amostras de helmintos que fazem parte da Coleção Helmintológica do Instituto Oswaldo Cruz. Carryng on the work related to the Brazilian Procamallanus, we rectify a few statements as well as confirm several ones appraising former species proposed and inserted in this paper and arise a new one. 1. procamallanus (S.) solani n. sp. was related to the nearest four brazilian species and their relationship is displaied on table I. 2 Procamallanus (S.)inheringi Travassos, Artigas & Pereira, 1928. The aspect of buccal capsule in males and females of our material was absolutely not that one described by Travassos & cols., since they were mistaken in their description, inverting the number of spiral thickenings in the buccal capsule of the latter. In order to compare our material with that assigned as type, we present camera lucida drawings and photomicrographies of both samples. 3. Procamallanus (S.) inopinatus Travassos, Artigas & Pereira, 1928. Its description and drawings were abridged and adapted from Pinto & Noronha, 1972. 4. Procamallanus (S.) amarali Vaz & Pereira, 1934. We found among fully males of the species, only tiny and diaphanous immature female nematodes in which we could observe the genitalia and buccal capsule in several developing phases. A sole young female speciment, owing a very short, smooth and thin walled ovejector was the basis for the description we present.